Self-reported early detection activities for breast cancer in Colombia in 2010: impact of socioeconomic and demographic characteristics - Anna Font-Gonzalez (Salud Pública de México, 2013)
Objective . To explore which socioeconomic and demogra - phic characteristics influence Colombian women to utilize screening mammography (SMMG). Materials and methods . Data of women aged 40-49 years (n=12 345) and 50-69 years (n=14 771) from the Colombian national survey of demography and health 2010 was analyzed. Risk estimates (odds ratios, OR) of self-reported SMMG use were obtained using logistic regression. Results . Among women aged 50-69 years, high wealth index (OR=4.7; CI 95%, 3.9-5.8), affiliation to special or contributory health insurance regime (OR=3.4; CI 95% 2.6-4.6 and OR=2.5; CI 95% 2.1-3.0 respectively), health consultation in previous year (OR=2.7; CI 95% 2.3-3.1), high education level (OR=2.3; CI 95% 1.8-2.9) and very good self- reported health (OR=1.5; CI 95% 1.1-2.0) positively influenced SMMG utilization. Among women aged 40-49 years, likelihood of having a SMMG was high after a health consultation in the previous year. Conclusions . Socioeconomic and demogra - phic differences in use of SMMG need to be contemplated in screening recommendations before considering an organized population-based programme.